The Face Inversion Effect Following Pitch and Yaw Rotations: Investigating the Boundaries of Holistic Processing - Favelle, Simone; Palmisano, Stephen (Frontiers in Psychology, 2012)
Upright faces are thought to be processed holistically. However, the range of views within which holistic processing occurs is unknown. Recent research by McKone (2008) suggests that holistic processing occurs for all yaw rotated face views (i.e. full-face through to profile). Here we examined whether holistic processing occurs for pitch, as well as yaw, rotated face views. In this face recognition experiment: (i) participants made same/different judgments about two sequentially presented faces (either both upright or both inverted); (ii) the test face was pitch/yaw rotated by between 0°-75° from the encoding face (always a full face view). Our logic was as follows: If a particular pitch/yaw rotated face view is being processed holistically when upright, then this processing should be disrupted by inversion. Consistent with previous research, significant face inversion effects (FIEs) were found for all yaw rotated views. However, while FIEs were found for pitch rotations up to 45°, none were observed for 75° pitch rotations (rotated either above or below the full face). We conclude that holistic processing does not occur for all views of upright faces (e.g., not for uncommon pitch rotated views), only those that can be matched to a generic global representation of a face.